2018
DOI: 10.3389/fendo.2018.00601
|View full text |Cite
|
Sign up to set email alerts
|

IGFBP-5 Promotes Fibrosis via Increasing Its Own Expression and That of Other Pro-fibrotic Mediators

Abstract: Pulmonary fibrosis is a hallmark of diseases such as systemic sclerosis (SSc, scleroderma) and idiopathic pulmonary fibrosis (IPF). To date, the therapeutic options for patients with pulmonary fibrosis are limited, and organ transplantation remains the most effective option. Insulin-like growth factor-binding protein 5 (IGFBP-5) is a conserved member of the IGFBP family of proteins that is overexpressed in SSc and IPF. In this study, we demonstrate that both exogenous and adenovirally expressed IGFBP-5 promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 50 publications
7
55
0
Order By: Relevance
“…Findings with IGFBP2 are consistent with our previous studies showing increased expression of IGFBP3 and IGFBP5 in IPF and SSc-PF (25,26) and reinforced the crucial role that IGFBPs and the IGF pathway play in the development and perpetuation of pulmonary fibrosis (22)(23)(24). Note however that IGFBPs can also signal via membrane bound proteins such as integrins in a IGF-independent pathway (59).…”
Section: Targeting Igfbp2 and Igfl2supporting
confidence: 90%
See 1 more Smart Citation
“…Findings with IGFBP2 are consistent with our previous studies showing increased expression of IGFBP3 and IGFBP5 in IPF and SSc-PF (25,26) and reinforced the crucial role that IGFBPs and the IGF pathway play in the development and perpetuation of pulmonary fibrosis (22)(23)(24). Note however that IGFBPs can also signal via membrane bound proteins such as integrins in a IGF-independent pathway (59).…”
Section: Targeting Igfbp2 and Igfl2supporting
confidence: 90%
“…We and others have previously shown that the insulin-like growth factors (IGFs) and their binding proteins (IGFBPs) are key players in the development and progression of pulmonary fibrosis (22)(23)(24)(25)(26)(27). IGFBP3, IGFBP5, and IGFBP7 have been previously shown to be upregulated in both lung tissues and lung fibroblasts from patients with SSc-PF and IPF (24)(25)(26). IGFBP4 is downregulated in SSc lung fibroblasts (27), and upregulated in IPF lung tissues (28,29).…”
Section: Upregulation Of Igfbp2 and Igfl2 Is Common To Both Diseasesmentioning
confidence: 99%
“…Exogenous and endogenously expressed IGFBP-5 was found to increase the expression of ECM component genes and pro-fibrotic genes in primary human IPF fibroblasts in vitro (150). IGFBP-5 was also shown to increase expression of its own gene in these cells, leading to a positive feedback loop that may play a role in IPF pathogenesis (150).…”
Section: Igfbp-5 In Pathology and Disease Statesmentioning
confidence: 99%
“…IGFBP-5 binds to endothelial cell monolayers by its cysteine residues [20] and could act in tissue remodeling. It also stimulates collagen production and upregulates extracellular matrix genes [21] and is reported to inhibit phosphorylation of ERK1/2, and p38-MAPK kinases. [22] EFEMP1 encodes glycoproteins composing the extracellular matrix component.…”
Section: Plos Onementioning
confidence: 99%